IMPROVING AGRICULTURAL RESILIENCE TO CLIMATE CHANGE THROUGH SOIL MANAGEMENT - Fahmuddin Agus; Husnain Husnain; Rahmah Dewi Yustika (Badan Penelitian dan Pengembangan Pertanian, 2015)
Climate change affects soil properties and hence crop growth. Several soil management practices potentially reduce vulnerability to unfavorable climate conditions. This paper reviews how climate change affects soil properties and how should soil management be tailored to increase adaptation capacity to extreme climatic conditions. The main symptoms of climate change such as the increase in the global atmospheric temperature, unpredictable onset of the wet and dry seasons and excessive or substantial decrease in rainfall are unfavorable conditions that affect crop growth and production. Several approaches, singly or a combination of two or more measures, can be selected to adapt to the climate change. These include conservation tillage, vegetative and engineering soil conservation, mulching, water harvesting, nutrient management, soil amelioration and soil biological management. Management of soil organic matter is very central in adapting to climate change because of its important role in improving water holding capacity, increasing soil infiltration capacity and soil percolation, buffering soil temperature, improving soil fertility and enhancing soil microbial activities. Organic matter management and other soil management and conservation practices discussed in this paper are relatively simple and have long been known, but often ignored. This paper reemphasizes the importance of those practices for sustaining agriculture amid the ever more serious effects of climate change on agriculture.